Differential Expression of Major Royal Jelly Proteins in the Hypopharyngeal Glands of the Honeybee Apis mellifera upon Bacterial Ingestion - Yun-Hui Kim; Bo-Yeon Kim; Jin-Myung Kim; Yong-Soo Choi; Man-Young Lee; Kwang-Sik Lee; Byung-Rae Jin (Insects, 2022)
Honeybee vitellogenin (Vg) transports pathogen fragments from the gut to the hypopharyngeal glands and is also used by nurse bees to synthesize royal jelly (RJ), which serves as a vehicle for transferring pathogen fragments to the queen and young larvae. The proteomic profile of RJ from bacterial-challenged and control colonies was compared using mass spectrometry; however, the expression changes of major royal jelly proteins (MRJPs) in hypopharyngeal glands of the honeybee Apis mellifera in response to bacterial ingestion is not well-characterized. In this study, we investigated the expression patterns of Vg in the fat body and MRJPs 1–7 in the hypopharyngeal glands of nurse bees after feeding them live or heat-killed Paenibacillus larvae. The expression levels of MRJPs and defensin-1 in the hypopharyngeal glands were upregulated along with Vg in the fat body of nurse bees fed with live or heat-killed P. larvae over 12 h or 24 h. We observed that the expression patterns of MRJPs and defensin-1 in the hypopharyngeal glands and Vg in the fat body of nurse bees upon bacterial ingestion were differentially expressed depending on the bacterial status and the time since bacterial ingestion. In addition, the AMP genes had increased expression in young larvae fed heat-killed P. larvae. Thus, our findings indicate that bacterial ingestion upregulates the transcriptional expression of MRJPs in the hypopharyngeal glands as well as Vg in the fat body of A. mellifera nurse bees.